2003
DOI: 10.1007/bf02893382
|View full text |Cite
|
Sign up to set email alerts
|

Significance of p53, Bcl-2, and HER-2/neu protein expression in Omani Arab females with breast cancer

Abstract: Racial disparity in the presentation of breast cancer and the outcome of its treatment is well established. However, the causes remain unexplained. The scarcity of reports about the prognostic significance of p53, bcl-2, and HER-2/neu in Arab females with breast cancer has been the impetus to this study. We evaluated the prognostic significance of altered expression of p53, bcl-2, HER-2/neu in Omani Arab females with non-metastatic breast cancer with correlation to other established prognostic factors. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
5
15
1
Order By: Relevance
“…This finding is similar to studies of Mansour Al-Moundhri et al 13 (49.6 years), Azizun-Nisa et al 14 In the present study majority of the cases (64%) had the tumour size ranging from 2 -5 cms followed by 14 (28%) cases of tumour size of > 5 cms. In the study by Azizun-Nisa et al 14 also, 52.7% of tumour were between 2 -5 cms and 35.3% were > 5 cms.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is similar to studies of Mansour Al-Moundhri et al 13 (49.6 years), Azizun-Nisa et al 14 In the present study majority of the cases (64%) had the tumour size ranging from 2 -5 cms followed by 14 (28%) cases of tumour size of > 5 cms. In the study by Azizun-Nisa et al 14 also, 52.7% of tumour were between 2 -5 cms and 35.3% were > 5 cms.…”
Section: Discussionsupporting
confidence: 82%
“…A study by Al-Moundhri et al 13 Tumour size is one of the most useful predictors of behaviour of breast carcinoma. In the present study, while correlating the HER2/neu positivity with the size of the tumour, majority was seen in with the tumour size between 2 -5 cms (50%) followed by 35.7%.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Age at menarche, age at menopause Our finding regarding the age at Menarche and Menopause is corroborative with a retrospective analysis of breast cancer cases conducted by Siddiqui T et al, who showed the age of menarche and the age of Menopause has no statistical significance between the HER-2/neu positive and the HER-2/neu negative Breast cancer in the population. 14 Number of full term pregnancy, age at first full term pregnancy, parity, family history of ovarian/breast cancer among first degree relatives, site of lump (left /right/bilateral), skin-nipple areola involvement.…”
Section: Menstrual Statussupporting
confidence: 78%
“…Al-Moundhri et al (23) found p53 overexpression in 41.7% of breast tumors examined with statistical significance. They also reported that p53 accumulation is related to poor tumor differentiation in human breast cancer (23).…”
Section: Discussionmentioning
confidence: 93%
“…IHC using the streptavidin-biotinperoxidase method was performed on paraffin-embedded tissue using the anti-p53 mouse monoclonal antibody, DO-1 (diluted 1:100), which recognizes the N-terminus of the human p53 protein (amino acids [21][22][23]. In addition, the antibody reacted with both wild-type and many mutant p53 proteins.…”
Section: Serological Analysismentioning
confidence: 99%